Peptide Nucleic Acid Promotes Systemic Dystrophin Expression and Functional Rescue in Dystrophin-deficient mdx Mice - Xianjun Gao; Xiaoyong Shen; Xue Dong; Ning Ran; Gang Han; Limin Cao; Ben Gu; HaiFang Yin (Elsevier, 2015)
Antisense oligonucleotide (AO)-mediated exon-skipping therapeutics shows great promise for Duchenne muscular dystrophy (DMD) patients. However, recent failure with drisapersen, an AO candidate drug in phase 3 trial, highlights the importance of exploring other effective AO chemistries for DMD. Previously, we demonstrated the appreciable biological activity of peptide nucleic acid (PNA) AOs in restoring dystrophin expression in dystrophin-deficient mdx mice intramuscularly. Here, we further explore the systemic potential and feasibility of PNA AOs in mediating exon skipping in mdx mice as a comprehensive systemic evaluation remains lacking. Systemic delivery of PNA AOs resulted in therapeutic level of dystrophin expression in body-wide peripheral muscles and improved dystrophic pathology in mdx mice without any detectable toxicity. Up to 40% of dystrophin restoration was achieved in gastrocnemius, to a less extent with other skeletal muscles, with no dystrophin in heart. Notably, comparable systemic activity was obtained between PNA AOs and phosphorodiamidate morpholino oligomer, a DMD AO chemistry in phase 3 clinical trial, under an identical dosing regimen. Overall, our data demonstrate that PNA is viable for DMD exon-skipping therapeutics with 20 mer showing the best combination of activity, solubility, and safety and further modifications to increase PNA aqueous solubility can enable longer, more effective therapeutics without the associated toxicity.